Hereditary deafness carrier screening in 9,993 Chinese individuals - Liu, Yanqiu; Wang, Lei; Yuan, Lanlai; Li, Yaqing; Chen, Zhengshi; Yang, Bicheng; Wang, Daqing; Sun, Yu (Frontiers in Genetics, 2024)
Background: Prenatal or prenatal carrier screening plays an important role in reproductive decision-making, but current research on hereditary deafness is limited. This study aimed to investigate the carrier frequencies of common deafness genes in the Chinese population who underwent carrier screening and to follow up on pregnancy outcomes in high-chance couples. Methods: Individual females or couples in preconception or early pregnancy were recruited from two hospitals in China. Carrier screening for common deafness genes in the Chinese population, including the GJB2 and SLC26A4 genes, was performed using next-generation sequencing technology. Genetic counseling was provided to subjects before and after testing. Results: Of the 9,993 subjects screened, the carrier rate was 2.86% for the GJB2 gene and 2.63% for the SLC26A4 gene. The variant with the highest carrier frequency in GJB2 was c.235delC (1.89%), and c.919-2A>G (1.08%) in SLC26A4. Of the six high-chance couples, four made alternative reproductive decisions (three with prenatal diagnosis and one with preimplantation genetic testing), with consequent termination of the birth of two affected fetuses. Conclusions: These findings confirmed the clinical utility of preconception or prenatal carrier screening for hereditary deafness.